2005
DOI: 10.2202/1548-923x.1052
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Clinical Reasoning in Undergraduate Nursing Students: Application and Evaluation of the Outcome Present State Test (OPT) Model of Clinical Reasoning

Abstract: 2005). Promoting clinical reasoning in undergraduate students: Application and evaluation of the Outcome Present State Test (OPT) model of clinical reasoning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 13 publications
(14 reference statements)
0
33
0
8
Order By: Relevance
“…3 Metacognition, which is the act of connecting knowledge and cognition, is a much more elusive facet of reasoning. The development and assessment of clinical reasoning skills have become focuses of education programs in several disciplines, including medicine, 4,7,8 nursing, 9,10 occupational therapy, 6,11,12 and physical therapy. 13 However, few researchers have investigated clinical reasoning during the athletic training clinical education process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 Metacognition, which is the act of connecting knowledge and cognition, is a much more elusive facet of reasoning. The development and assessment of clinical reasoning skills have become focuses of education programs in several disciplines, including medicine, 4,7,8 nursing, 9,10 occupational therapy, 6,11,12 and physical therapy. 13 However, few researchers have investigated clinical reasoning during the athletic training clinical education process.…”
mentioning
confidence: 99%
“…Several clinical reasoning techniques, including case studies, 6 journaling, 9 problem-based learning, 12 peer coaching, 13 and role play, 8 have been used to evaluate the expression of clinical reasoning in allied health and medical students. However, each technique has limitations.…”
mentioning
confidence: 99%
“…In this sense, nurses are able to note the nursing diagnosis with the most arrows in the web supporting that this diagnosis has an impact on the other related diagnoses in the patient's situation 32 . Explaining relationships among nursing diagnosis supports the development of clinical reasoning skills 33 .…”
Section: Discussionmentioning
confidence: 98%
“…NANDA-I, Inc. keystone issue was chosen for the patient was based on an analysis and synthesis of functional relationships among competing nursing diagnosis 32 . Thus, focus on the diagnosis Imbalanced nutrition: less than body requirements (00002) may resolve the related nursing diagnosis.…”
Section: Fig1 Application Of a Clinical Reasoning Web In One Patientmentioning
confidence: 99%
“…In educational environments, problem-solving models have been shown to support the development of clinical reasoning skills as well as process skills such as working as a team to define problems, explain solutions, and evaluate solution outcomes. [14][15][16] To date, little research has been reported on the implementation of the PPCP in pharmacy education. In a search of literature through the EBSCOHost Multi-search database aggregator using the term "pharmacists' patient care process", 12 articles were identified, of which only 1 reported on the use of the PPCP as an instructional tool.…”
mentioning
confidence: 99%